Assessing presence in virtual environments: adaptation of the psychometric properties of the presence questionnaire to the portuguese populations - Vasconcelos-Raposo, José (2018)
Virtual Reality applications have the goal of transporting their users to a given virtual environment (VE). Thus, Presence is a consensual metric for evaluating the VEs’ effectiveness. The present study adapts the Presence Questionnaire (PQ) for the Portuguese-speaking population, maintaining the validity of the contents and concepts, to ascertain the psychometric properties of the instrument.The adaptation to Portuguese was achieved through the standard adaptation process of translation and back-translation process. The sample consisted of 451 individuals (268 males and 183 females). Factor reliability ranged from 0.63 to 0.86. Confirmatory factor analysis produced a theoretical model of 21 items distributed among seven factors, where the covariance between some residual item errors was established. The fit indices obtained were x2/df = 2.077, GFI = 0.936, CFI = 0.937, RMSEA = 0.049, P [RMSEA ≤ 0.05], MECVI = 1.070. Results obtained allowed us to consider that the adapted Portuguese version of the PQ, with 21 items, forms a robust and valid questionnaire whose use is recommended to evaluate Presence in virtual reality research programmes, provided that they use samples of the Portuguese language (Europe).